The fNIRS evaluation of frontal and temporal lobe cortical activation in Chinese first-episode medication-naïve and recurrent depression during a verbal fluency task - Yang, Ting; Wang, Hongyu; Dai, Haiyue; Hui, Juan; Zhang, Jintong; Li, Juan; Cui, Guimei; Wang, Juan; Mu, Junlin; Zhang, Zhaohui (Frontiers in Psychiatry, 2023)
Background: Functional near-infrared spectroscopy (fNIRS) identifies neurophysiological differences between psychiatric disorders by assessing cortical hemodynamic function. Few trials have studied differences in brain functional activity between first-episode medication-naïve depression patients (FMD) and recurrent major depression (RMD). We aimed to determine the differences between FMD and RMD in oxygenated hemoglobin concentration ([oxyHb]), and to investigate the correlation between frontotemporal cortex activation and clinical symptoms. Methods: We recruited 40 patients with FMD, 53 with RMD, and 38 healthy controls (HCs) from May 2021 to April 2022. Symptom severity was assessed with the 24-item Hamilton Depression Rating Scale (HAM-D) and the Hamilton Anxiety Rating Scale (HAM-A). A 52-channel fNIRS measured changes in [oxyHb] during VFT performance. Results: Both patient groups performed poorly during the VFT task compared with HC (FDR p < 0.05), but there was no significant difference between the two patient groups. Analysis of variance showed that mean [oxy-Hb] activation was lower in both the frontal and temporal lobes in the MDD group compared with HCs (FDR p < 0.05). Additionally, patients with RMD had a significantly lower hemodynamic response in the right dorsolateral prefrontal cortex (DLPFC) and dorsal frontal pole cortex (DFPC) than patients with FMD (FDR p < 0.05). No significant correlation was found between changes in mean [oxy-Hb] and either medical history or clinical symptoms (FDR p < 0.05). Conclusions: The presence of different neurofunctional activity in some of the same brain regions in FMD and RMD patients implied a link between the level of complexity activation in frontal regions and the stage of MDD. Cognitive impairment may already be present at the beginning of an MDD episode.